Correlation between support foot placement and goal accuracy for instep kicks in the soccer field - Petrone, N.; Marcolin, G.; Robazza, C. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of the present work was to evaluate the correlation between the placement of the support foot on the ground and the precision of the shot: the placement of the support foot relative to the ball was supposed to have an effect on the shot precision for a given target. The goal was divided with a visual grid enabling to identify six possible targets of the shot, high/low for vertical placement and left/center/right for horizontal placement. Skilled players were asked to perform repetitive penalty instep kicking in the soccer field with a defined target such as high/left or low/right: ground reaction loads were recorded by means of a force platform installed in a suitable board and the movement was video recorded. The position of COP at the kick instant with respect to the ball and the average trajectory of COP on the platform resulted to be correlated with successful target in such a way that training procedures can be defined to improve the player coordination for precision shooting. Finally, differences between free kicking and kicking with a goalkeeper were recorded, enabling to analyze a realistic player behaviour in the study.